New Governance in the European Union: Omc - Aliu, Ylber (Mediterranean Journal of Social Sciences, 2022)
The main purpose of this paper is to study the new governance in the European Union: the open method of coordination (hereinafter: OMC). Some of the main features of the OMC are: an instrument of spreading the best practices of achieving the EU's main goals; to help member states develop their policies; creating a calendar for achieving project goals: short, medium and long term; translating European guidelines into national and regional policies specifying objectives and measures; as well as periodic monitoring and evaluation. The main value of the OMC is all involvement in decision-making: European Union institutions, civil society, interest groups, media, etc., through the OMC play a role in the process of drafting public policies and monitoring and evaluating implementation. The OMC aims to complement the 'democratic deficit' of EU institutions, especially in the education policy, employment policies and social welfare policies. We have used two methods for research of the paper. The first, the method of research of scientific and academic literature related to the European Union. Second, the case study of individual cases for displaying the new governance format: OMC in the European Union. The result of the research is to understand what new governance in the European Union is, when it comes to expression of this form of governance, who are the main actors in implementing new governance, when it has started to apply, etc. The conclusion of the paper is that the new governance in the European Union: the OMC has transformed the decision-making process as well as the process of drafting policies, strategies and legislation within the EU. Received: 26 October 2021 / Accepted: 15 December 2021 / Published: 5 January 2022